2015
DOI: 10.1128/aem.03678-14
|View full text |Cite
|
Sign up to set email alerts
|

Effective Trapping of Fruit Flies with Cultures of Metabolically Modified Acetic Acid Bacteria

Abstract: c Acetoin in vinegar is an attractant to fruit flies when combined with acetic acid. To make vinegar more effective in attracting fruit flies with increased acetoin production, Komagataeibacter europaeus KGMA0119 was modified by specific gene disruption of the acetohydroxyacid isomeroreductase gene (ilvC). A previously constructed mutant lacking the putative ligand-sensing region in the leucine-responsive regulatory protein (KeLrp, encoded by Kelrp) was also used. The ilvC and Kelrp disruptants (KGMA5511 and K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
2
7
1
Order By: Relevance
“…There were no significant differences between BRV+RW and ACV+RW, suggesting that BRV+RW may be equivalent to ACV+RW as an olfactory attractant for D. suzukii . Similar to the results of previous experiments, the use of ACV+RW resulted in greater D. suzukii captures than ACV alone [32,46]. Researchers conducting field experiments in berry crops found that wine-vinegar blends were more attractive to D. suzukii than wine and vinegar alone [46] or aqueous red wine [32].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…There were no significant differences between BRV+RW and ACV+RW, suggesting that BRV+RW may be equivalent to ACV+RW as an olfactory attractant for D. suzukii . Similar to the results of previous experiments, the use of ACV+RW resulted in greater D. suzukii captures than ACV alone [32,46]. Researchers conducting field experiments in berry crops found that wine-vinegar blends were more attractive to D. suzukii than wine and vinegar alone [46] or aqueous red wine [32].…”
Section: Discussionsupporting
confidence: 70%
“…Previous research has demonstrated that apple cider vinegar [49,50] and apple cider vinegar and red wine [51] are effective field attractants for D. suzukii and Z. indianus . Rice vinegar, with and without red wine, has also been characterized by several researchers [30,32,46]. Recently, Akasaka et al [52] demonstrated that brown rice vinegar was more attractive to D. suzukii than apple cider vinegar in laboratory choice assays, substantiating the need for the characterization of attractant efficacy in field settings.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Quantification of the polyamines, organic acids, and ethanol by HPLC and GC. The polyamines and organic acids or ethanol in the culture supernatants were quantified using HPLC or GC, respectively, as previously described (47,53). To extract the polyamines, 1/10 volume of 10% (wt/vol) TCA was added to the samples and thoroughly vortexed.…”
Section: Methodsmentioning
confidence: 99%
“…Huang et al (2017) also showed combination baits of yeastwine-vinegar-sugar mixtures are superior attractants compared to wine-vinegar alone. Ishii et al (2015) genetically modified the acetic acid bacterium (AAB) Komagataeibacter europaeus with increased acetoin (a key ingredient in vinegar) production and was able to trap significantly more Drosophila using the mutant strain compared to other strains loaded on sticky traps. Similarly, microbial semiochemicals have been shown to attract tephritid fruit flies.…”
Section: Polyhedral Capsid Suspension Concentration Of Virusmentioning
confidence: 99%